2011
DOI: 10.1007/s00464-010-1552-6
|View full text |Cite
|
Sign up to set email alerts
|

Biliary metal stents are superior to plastic stents for preoperative biliary decompression in pancreatic cancer

Abstract: BackgroundIt is unclear whether plastic or metal stents are more suitable for preoperative biliary decompression in pancreatic cancer. The objective of this study was to compare the rate of endoscopic reinterventions in patients with pancreatic cancer undergoing plastic or self-expandable metal stent (SEMS) placements for preoperative biliary decompression.MethodsThis was a retrospective study of all patients with obstructive jaundice secondary to pancreatic head cancer who underwent their index endoscopic ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 13 publications
4
60
0
1
Order By: Relevance
“…According to previous studies (Decker et al, 2011;Adams et al, 2012), pancreatic cancer patients who received metal stent biliary drainage had a better patency, and lower incidence of complications than those treated by plastic biliary stent. Therefore, in this study, all patients were treated with metal stent biliary drainage, and the results showed that jaundice was significantly improved a week after the biliary drainage to basically normal total bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies (Decker et al, 2011;Adams et al, 2012), pancreatic cancer patients who received metal stent biliary drainage had a better patency, and lower incidence of complications than those treated by plastic biliary stent. Therefore, in this study, all patients were treated with metal stent biliary drainage, and the results showed that jaundice was significantly improved a week after the biliary drainage to basically normal total bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study compared the outcome of 29 patients who underwent PBD with plastic stents (n ¼ 18) or SEMS (n ¼ 11); endoscopic reintervention was required in 39% of the plastic stent group awaiting surgery, but no reintervention was required in the SEMS group. 64 Furthermore, a multicenter randomized controlled trial found that SEMS had an longer patency than plastic stents. 65 This study was performed in palliative patients.…”
Section: Stent Selection: Plastic Versus Metalmentioning
confidence: 99%
“…Therefore, current recommendations for consideration of preoperative biliary drainage/stent include patients with the following symptoms/complications-cholangitis, severe intractable pruritus, and coagulopathyand those who will not undergo immediate surgical resection [ 32 , 33 ]. Self-expanding metallic stents are preferred over plastic ones [ 36 ].…”
Section: Preoperative Biliary Drainage/stentmentioning
confidence: 99%